PENGARUH MEDIA SMART BOX DENGAN MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA KELAS II SD NEGERI TUGUREJO 02 MATERI PENERAPAN NILAI PANCASILA - Alya Putri Maradika; Eni Kumalasari; Wulan Aulia Azizah; Susilo Tri Widodo; Anita Nurkhikmah (STKIP Subang, 2023)
This research aims to find out the effect of implementing the project based learning model and smart box media in Pancasila Education subjects. The location of the research was carried out at SD Negeri Tugurejo 02 with the research subjects being class II students, totaling 26 students. This type of research is experimental research. Data analysis used the normality test, N Gain test and t test (t test) with the help of SPSS 26 software. The results of the research showed that there was an increase in learning outcomes for students using smart box media and the project based learning model in Pancasila education learning for class II elementary school. Negeri Tugurejo 02. This is proven by the increase in the average results of the pretest and posttest that have been carried out. In the initial test or pretest, students got an average score of 51.34, while in the final test or posttest, students got an average score of 73.07. The effect of the increase can also be seen from the results of hypothesis testing, namely obtained tcount = 9.506 while ttable = 2.060 which indicates that there is a quite significant influence and Ha is declared acceptable.